Morning Assembly Contribution Towards Positive Character Formation Of Students at Primary Education - Holiah, Siti; Amanaturrahmah , Isna; Magfriani, Meitha Rohanisa; Nurmawati; Sari, Vina Novita (R-Disa: Riset Inovasi Pendidikan Guru Sekolah Dasar, 2026)
This study aims to determine the contribution of morning assembly activities in realizing good character and noble character in students of SDN A. This study uses a qualitative method with a qualitative descriptive approach located at SDN A. The data obtained in this study through observation and questionnaire activities that have been answered by 85% of students with a total of 90% assuming positively. The subjects in this study were students of SDN A, based on the research conducted, the results obtained that routine morning assembly activities at SDN A can be used as an effective means and path to form and instill good character and character in children such as discipline, responsibility, politeness, nationalism and mutual respect for fellow students and respect for teachers and friends